Identification of Topotactic Surface‐Confined Ullmann‐Polymerization. Issue 41 (3rd September 2021) - Dettmann, Dominik; Galeotti, Gianluca; MacLean, Oliver; Tomellini, Massimo; Di Giovannantonio, Marco; Lipton‐Duffin, Josh; Verdini, Alberto; Floreano, Luca; Fagot‐Revurat, Yannick; Perepichka, Dmitrii F.; Rosei, Federico; Contini, Giorgio
Abstract: On‐surface Ullmann coupling is an established method for the synthesis of 1D and 2D organic structures. A key limitation to obtaining ordered polymers is the uncertainty in the final structure for coupling via random diffusion of reactants over the substrate, which leads to polymorphism and defects. Here, a topotactic polymerization on Cu(110) in a series of differently‐halogenated para‐phenylenes is identified, where the self‐assembled organometallic (OM) reactants of diiodobenzene couple directly into a single, deterministic product, whereas the other precursors follow a diffusion driven reaction. The topotactic mechanism is the result of the structure of the iodine on Cu(110), which controls the orientation of the OM reactants and intermediates to be the same as the final polymer chains. Temperature‐programmed X‐ray photoelectron spectroscopy and kinetic modeling reflect the differences in the polymerization regimes, and the effects of the OM chain alignments and halogens are disentangled by Nudged Elastic Band calculations. It is found that the repulsion or attraction between chains and halogens drive the polymerization to be either diffusive or topotactic. These results provide detailed insights into on‐surface reaction mechanisms and prove the possibility of harnessing topotactic reactions in surface‐confined Ullmann polymerization. Abstract : Real‐time spectroscopy and computed reaction pathway investigations of on‐surface Ullmann reaction of a series of aryl halides reveals topotactic kinetics in the formation of poly‐para phenylene chains, which is driven by alignment of reaction sites instead of random diffusion of the organic species.